2021
DOI: 10.14309/ctg.0000000000000364
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric and Metabolic Endoscopy: A New Paradigm

Abstract: The prevalence of obesity, type 2 diabetes mellitus, and metabolic syndromes is increasing globally. Minimally invasive metabobariatric (MB) endoscopic therapies are adjunct treatments that can potentially bridge the gap between surgical interventions and medical therapy. A growing number of MB techniques are becoming available, allowing for more personalized and patient-targeted treatment options for specific disease states. MB techniques are less invasive than surgery and can precisely target different parts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…[ 23 24 ] Several randomized and non-randomized studies have shown the benefits of EIBT in terms of weight reduction in obese patients. [ 18 19 25 26 27 28 29 30 31 32 33 34 ] In contrast, other studies concluded that EIBT did not seem to be an effective method for achieving weight loss. [ 35 36 37 38 ] The disappointing results of some of these initial reports may indicate a flaw in the technique, poor choice of patients, or lack of dietician follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 24 ] Several randomized and non-randomized studies have shown the benefits of EIBT in terms of weight reduction in obese patients. [ 18 19 25 26 27 28 29 30 31 32 33 34 ] In contrast, other studies concluded that EIBT did not seem to be an effective method for achieving weight loss. [ 35 36 37 38 ] The disappointing results of some of these initial reports may indicate a flaw in the technique, poor choice of patients, or lack of dietician follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The intragastric balloon, duodenal mucosal resurfacing, and bariatric surgeries are among them. These procedures are indicated according to the degree of obesity, comorbidities, and the therapeutic effect sought [ 41 , 42 ].…”
Section: Obesity: Epidemiology Diagnosis and Treatmentmentioning
confidence: 99%
“…On the other hand, primary obesity surgery endoluminal (POSE) is performed with the IOP system. It is a more complex device, equipped with a 54 Fr handle-controlled tube (TransPort ® ) able to be maneuvered in four directions and with four channels that house specialized instruments for grasping tissue folds (g-Lix™ and g-Prox EZ ® ) for positioning tissue anchors (g-Cath EZ™), and for lumen visualization with an ultra-slim endoscope [ 50 , 51 ].…”
Section: Primary Bariatric Endoscopic Therapiesmentioning
confidence: 99%